FAMILY MILICHIIDAE - Swann, John (Zootaxa, 2016)
This catalog summarizes information on the species of Milichiidae known to occur in Colombia. It includes 6 described species in 3 described genera and 6 undescribed species in two genera, one of which is also undescribed.